Modelo de sistema de gestão da qualidade para propriedades rurais leiteiras. - Lima, Luciano Silva (2004)
The agents of Brazilian dairy production chain work with critical rates of losses, starting from the dairy rural company that, several times, supply raw material characterized by low quality. This low quality may be justified by problems with planning, execution and control of daily activities in the farm. In this context, the present dissertation proposes a reference model of Quality Management System (QMS) for dairy farms. The model´s aim is establish the quality management requirements and the principles needed to assure the quality and security of milk, as well as needed to the continuous improvement of the process activities. The model contents two modules: Basis Module is shaped by a set of principles and conditions that orient all the system, while Requirements Module is shaped by a set of requirements that execute and manage the system in the practice based on data and facts generating decisions and plans in the daily of dairy farm. Farther on showing the modules details, this work presents a proposal of the QMS documentation structure and also a set of suggestions to the model implementation in the dairy farms. With its implementation, the model may minimize costs with losses and reworks, and generate higher satisfaction to the farm´s customers (industrial establishments) and final consumers of chain. According to the assessment realized with a sample of the target public (farmers and rural extension agents), the model accomplishes its purpose. Although its language had been evaluated as a weakness, the QMS was considered an important mean to the Brazilian dairy farmers get a professional status.